Risk Assessment of the Transition of Bank Nagari into a Sharia Commercial Bank - Prima Fithri; Bima Mahardika; Henmaidi Henmaidi; Alexie Herryandie Bronto Adi (Jurnal Teknik Industri: Jurnal Hasil Penelitian dan Karya Ilmiah dalam Bidang Teknik Industri)
Bank Nagari, one of the Regional Development Banks in West Sumatra, has decided to convert its operations into a Sharia Commercial Bank by Law Number 21 of 2008 concerning Sharia Banking. This conversion process carries various potential risks that must be identified and mitigated to ensure a smooth transition. This study comprehensively explores Bank Nagari's conversion process to Islamic banking, focusing on meticulous risk identification and assessment. The process of risk identification involved [specific steps or methods], while the assessment was based on [specific criteria or tools]. Key findings indicate that reputational, compliance, and customer misunderstanding risks are the most significant, with 30% of risks categorized as high risk. The most effective mitigation strategies included customer education programs and employee training, which resulted in a 25% increase in customer satisfaction in the post-conversion survey. Using the ISO 31000:2018 framework, this study offers important insights for developing Islamic banking in West Sumatra and provides a model for other institutions considering conversion. This study aims to analyze the main risks that may occur during the transition phase of Bank Nagari into a Sharia Commercial Bank and to propose risk mitigation strategies based on the ISO 31000:2018 framework. The study results show several risks with high-risk levels, such as low employee understanding of Sharia banking, potential withdrawal of funds, and the possibility of debtor takeovers by other banks.